Acute kidney injury in major gynaecological surgery: an observational study. (19th August 2014) - Vaught, AJ; Ozrazgat‐Baslanti, T; Javed, A; Morgan, L; Hobson, CE; Bihorac, A
<x xml:space="preserve">Abstract</x> Objective To assess the prevalence, outcomes and cost associated with acute kidney injury (AKI) defined by consensus risk, injury, failure, loss, and end‐stage kidney (RIFLE) criteria after gynaecologic surgery. Design Retrospective single‐centre cohort study. Setting Academic medical centre. Sample Two thousand three hundred and forty‐one adult women undergoing major inpatient gynaecologic surgery between January 2000 and November 2010. Methods AKI was defined by RIFLE criteria as an increase in serum creatinine greater than or equal to 50% from the reference creatinine. We used multivariable regression analyses to determine the association between perioperative factors, AKI, mortality and cost. Main outcome measures AKI, combined major adverse events (hospital mortality, sepsis or mechanical ventilation), 90‐day mortality and hospital cost. Results Overall prevalence of AKI was 13%. The prevalence of AKI was associated with the primary diagnosis. Of women with benign tumour surgeries, 5% (43/801) experienced AKI compared with 18% (211/1159) of women with malignant disease (P < 0.001). Only 1.3% of the whole cohort had evidence of urologic mechanical injury. In a multivariable logistic regression analysis, AKI patients had nine times the odds of a major adverse event compared to patients without AKI (adjusted odds ratio 8.95, 95% confidence interval 5.27–15.22). We have identified several readily available perioperative factors that can be used to identify patients at high risk for AKI after in‐hospital gynaecologic surgery. Conclusions AKI is a common complication after major inpatient gynaecologic surgery associated with an increase in resource utilisation and hospital cost, morbidity and mortality.